EFEKTIVITAS MODEL PEMBELAJARAN MAKE A MATCH UNTUK MENGIDENTIFIKASI JENIS PEKERJAAN PADA MATERI IPS DALAM TEMA 8 KELAS IV SDN KEDALON 02 BATANGAN - nurhayati, fitri (Malih Peddas (Majalah Ilmiah Pendidikan Dasar), 2020)
AbstractAbstract: This study aims to describe the effectiveness of make a match learning model to identifying the type of work on social science material in theme eight in fourth grade SDN Kedalon 02 Batangan. This study used pre-experimental design with one group pretest-posttest design. There is a significant influence on the treatment in the form of make a match learning model. This is evidenced from the calculation of T test using SPSS analysis 22. The result obtained from the calculation is the value of sig. (2-tailed) is 0.000 0,05. Thus, it can be concluded that by using make a match learning model is effective and influential to identifying type of work on the subject of social science in fourth grade in SDN Kedalon 02 Batangan Pati.Â Keywords: Effectiveness, Make a Match Learning Model, identifying the type of work